Addition of Carrot Flour to the Making of Mackerel Nuggets - Paldiari, Redo; Ayu, Dewi F; Rahmayuni, Rahmayuni (Universitas Pattimura, 2023)
The purpose of this study was to obtain the best formulation for the use of carrot flour in the making of mackerel fish nuggets based on the quality standard of SNI 7758-2013. The research method used a completely randomized design with four treatments and four replications. The treatments in the study consisted of KW1 (ratio of mackerel fish and carrot flour 80:20), KW2 (ratio of mackerel fish and carrot flour 70:30), KW3 (ratio of mackerel fish and carrot flour 60:40), and KW4 (ratio of mackerel fish and carrot flour 50:50). The data obtained were analyzed statistically using analysis of variance and continued with the Duncan’s New Multiple Range Test (α = 0.05). The results showed that the ratio of mackerel fish and carrot flour significantly affected moisture, ash, fat, protein crude fiber contents, and descriptive sensory assessments such as outer and inner color, scent, taste, texture, and overall hedonic assessment. The best treatment was KW1 (ratio of mackerel fish and carrot flour 80:20), which fulfilled the quality requirements of fish nuggets in terms of 55.43% moisture content, 2.17% ash, 5.11% fat, 18.13% protein, and 2.57% crude fiber content, with a description of greyish brown color, flavored with mackerel fish, a taste of mackerel fish, and a chewy texture.